2007
DOI: 10.1002/dvdy.21360
|View full text |Cite
|
Sign up to set email alerts
|

Genetic screen for regulators of ind expression identifies shrew as encoding a novel twisted gastrulation‐like protein involved in Dpp signaling

Abstract: Initiation and refinement of expression of the Ind homeodomain protein in the Drosophila embryo is coordinately regulated by global dorsoventral patterning pathways Dorsal, Egfr, and Dpp, and well as by Vnd, which positions the ventral boundary of Ind. Therefore, we set out to look for novel regulators of dorsoventral patterning by screening the Exelixis deficiency collection for modified expression of Ind. Indeed, we found deficiencies that remove components of the known signaling pathways had altered or lost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…While a number of screens have already made use of the Df collection (Bonds et al 2007) or the transposon insertion collection (Kankel et al 2007;Chang et al 2008;Shalaby et al 2009) individually, the logistics of obtaining and screening all of the 16,000 lines is not feasible for many labs. Thus, we applied a hierarchical strategy for our screen ( Figure 1A) that would take advantage of both collections and also would assay LOF vs. neomorphic effects.…”
Section: Resultsmentioning
confidence: 99%
“…While a number of screens have already made use of the Df collection (Bonds et al 2007) or the transposon insertion collection (Kankel et al 2007;Chang et al 2008;Shalaby et al 2009) individually, the logistics of obtaining and screening all of the 16,000 lines is not feasible for many labs. Thus, we applied a hierarchical strategy for our screen ( Figure 1A) that would take advantage of both collections and also would assay LOF vs. neomorphic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, genetic studies have revealed that Scw and Gbb interact with a distinct suite of extracellular modulators and have different affinities and preferences for the Type I receptors Tkv and Sax. In the early embryo, Scw signalling requires the Chordin orthologue Sog, the metalloprotease Tld, and the cysteinerich binding proteins Tsg and Srw, and is transduced by the Type I receptor Sax (Bonds et al 2007;Holley et al 1995;Neul and Ferguson 1998;Shimmi et al 2005a). In the pupal wing, Gbb signalling requires Sog, the metalloprotease Tok, and the cysteine-rich binding protein Cv, and is transduced primarily through the Type I receptor Tkv (Ray and Wharton 2001;Serpe et al 2005;Shimmi et al 2005a).…”
Section: A Unique Signalling Mode Has Evolved With Scwmentioning
confidence: 98%
“…Scw functions in the early embryo where it augments Dpp signalling along the dorsal-ventral axis to produce peak levels of BMP activity at the dorsal midline, thus, specifying cells that will become the extraembryonic amnioserosa (Arora et al 1994). Scw achieves this focusing of BMP activity by forming heterodimers with Dpp (Shimmi et al 2005b), interacting with a specific suite of extracellular modulators including the Chordin orthologue Short gastrulation (Sog), the metalloprotease Tolloid (Tld), and the cysteine-rich binding proteins Twisted gastrulation (Tsg) and Shrew (Srw) (Bonds et al 2007;Holley et al 1995;Neul and Ferguson 1998;O'Connor et al 2006;Shimmi and O'Connor 2003), and signalling through the Type I receptor Saxophone (Sax; Neul and Ferguson 1998;Nguyen et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…While we were not able to identify an orthologue of tok, the presence of a distinct tld orthologue in E. balteatus suggests that the dipteran gene duplication giving rise to tld and tok occurred before the origin of the amnioserosa (Figure 3D). BMP ligand activity in D. melanogaster is additionally modulated by Twisted gastrulation (Tsg) [51,52], Crossveinless (Cv) [53,54], Shrew (Srw) [26,55], as well as the membrane associated factors Crossveinless-2 (Cv-2) [56,57], Kekkon 5 (Kek5) [58], Pentagone (Pent) [59] and Larval Translucida (Ltl) [60]. We identified E. balteatus homologues of cv-2, kek5 (Figure 3E) as well as tsg, cv and an additional cv paralogue, Eba-cv-like (Figure 3F).…”
Section: Resultsmentioning
confidence: 99%